Effect of Five-Consecutive-Day Exposure to an Anxiogenic Stressor on Sleep-Wake Activity in Rats - O'Malley, Matthew W.; Fishman, Rachel Lea; Ciraulo, Domenic A.; Datta, Subimal (Frontiers in Neurology, 2013)
Repeated exposure to an anxiogenic stressor (AS) is a known environmental factor for the development of depression, yet the progression of sleep-wake (S-W) changes associated with the onset of AS-induced depression (ASID) is not completely understood. Thus, the aim of this study was to identify these progressive S-W changes by developing ASID in rats, via repeated exposure to an AS, and compare this ASID-associated sleep phenotype with the sleep phenotype of human depression. To achieve this aim, rats were first recorded for a 6-h period of baseline S-W activity without AS. Then, rats were subjected to five days of AS [Day 1: inescapable foot-shock; 5 trials of 3-s foot-shocks (1.0 mA) at 3-min intervals; Days 3-5: 15 trials of 5-s foot-shocks at 45-s intervals]. S-W activity was recorded for 6 h immediately after each AS treatment session. Two days later rats were again recorded for 6 h of S-W activity, but with no exposure to the AS (NASD). Compared to the baseline day: Day 1 of AS (ASD-1) increased wakefulness, slow-wave sleep (SWS) latency, and REM sleep latency, but decreased the total amount of REM sleep; ASD-2 animals remained awake throughout the 6-h S-W recording period; ASD-3, ASD-4, and ASD-5 (ASDs-3-5) decreased wakefulness, SWS latency, and REM sleep latency, but increased the total amount of REM sleep. Interestingly, these results reveal that initial exposure to the AS versus later, repeated exposure to the AS produced opposing S-W changes. On NASD, animals exhibited baseline-like S-W activity, except slightly less REM sleep. These results suggest that repeated AS produces a sleep phenotype that resembles the sleep phenotype of depression in humans, but consistent re-exposure to the AS is required. These results are promising because the methodological simplicity and reversibility of the ASID-associated S-W phenotype could be more advantageous than other animal models for studying the pathophysiological mechanisms that underlie the expression of ASID.